2011
DOI: 10.1158/0008-5472.can-10-1727
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome Breakage Is Regulated by the Interaction of the BLM Helicase and Topoisomerase IIα

Abstract: Cells deficient in the recQ-like helicase BLM are characterized by chromosome changes that suggest the disruption of normal mechanisms needed to resolve recombination intermediates and to maintain chromosome stability. Human BLM and topoisomerase IIα interact directly via amino acids 489-587 of BLM and co-localize predominantly in late G2- and M-phases of the cell cycle. Deletion of this region does not affect the inherent in vitro helicase activity of BLM but inhibits the topoisomerase IIα-dependent enhanceme… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(43 citation statements)
references
References 42 publications
2
41
0
Order By: Relevance
“…Previously, human topoisomerase II␣ and topoisomerase I were reported to inhibit the BLM and WRN helicases, respectively, through inhibition of their ATPase activity (43,44); in contrast, human TopoIII␣ had no effect on BLM ATPase activity (9). We found that the Hel112 DNA-independent ATPase activity was not affected by 2-fold molar excess of SsTop3 (Fig.…”
Section: Resultsmentioning
confidence: 52%
“…Previously, human topoisomerase II␣ and topoisomerase I were reported to inhibit the BLM and WRN helicases, respectively, through inhibition of their ATPase activity (43,44); in contrast, human TopoIII␣ had no effect on BLM ATPase activity (9). We found that the Hel112 DNA-independent ATPase activity was not affected by 2-fold molar excess of SsTop3 (Fig.…”
Section: Resultsmentioning
confidence: 52%
“…Recently, it was shown that BLM helicase and Topoisomerase IIα interact to maintain genomic integrity (24). Although this interaction served to stimulate BLM helicase activity, BLM helicase was not reported to stimulate DNA decatenation (24).…”
Section: Resultsmentioning
confidence: 99%
“…Stable depletion of RECQL5 inhibits cell proliferation and induces a G 2 /M checkpoint. BLM also interacts with Topo IIα, which is important in preventing chromosomal breakage (228). These observations indicate that RecQ helicases play significant roles in the resolution of late replication intermediates and DNA decatenation.…”
Section: Recq Helicases In Dna Replicationmentioning
confidence: 99%